(NsOBRANIE SO^INENIJ W DWENADCATI TOMAH(B; s (NiDIOT(B: [(NrOMAN(B] / s (N~ASTX (B7s - (NdOSTOEWSKIJ(B, (NfEDORs ((NmOSKWA(B: s (NpRAWDA(B, s, 1982)
(Nw SEDXMOJ TOM WO[LO OKON^ANIE ROMANA (B"(NiDIOT(B".s
rus
Keywords: (NpSIHOLOGI^ESKIJ ROMANs